Constitución Social de Honduras of Ramón Rosa and the validity of an epochal and identity perspective - Fajardo Salinas, José Manuel (2022)
In this paper a hermeneutic analysis of the work Constitución Social de Honduras by Ramón Rosa is made with the purpose of revealing features of the Honduran identity that underlie in thinkers of the XIX century in the context of the Liberal Reform. After introducing basic data on the author, the work and the historical period of its writing, the use of a hermeneutic instrument to analyze this text is presented and justified. This instrument divides the analysis into three thematic axes: anthropological, moral, and political; subsequently, applying categories of analysis appropriate to the phenomenon of nationality in the key to modernity, the contents of the text are interpreted from the three thematic axes mentioned, in order to extract identity features from a philosophical vision. Thus, this article is presented as a first approach to the conformation of the Honduran identity from a hermeneutic analysis.